Children Who Offend in Turkey: The Case of the Ankara Child Education Center - Çağlar, Türken (International journal of offender therapy and comparative criminology, 2025)
This paper investigates the underlying causes of children’s involvement in criminal behavior, and the rehabilitation programs which seek to reintegrate them into society after their release. The data needed were gathered from children’s case files and semi-structured interviews with professionals who work in a child education institution. The findings of the study, which include the demographic and socio-economic background of children who offend, the types of crimes they have committed, their causes, and the nature of the applied rehabilitation programs provided for the children who were serving their sentences in the education center are explained and discussed. It is found that these children are victims of social, cultural, economic, and political structures of the society. They are generally from migrants’ families with middle and low incomes and live in gecekondu neighborhoods.1 Poor living conditions, lack of parental affection, poverty, deprivation, neglect, abuse, addiction, the lack of preventive and protective institutions, the lack of NGOs which work with children, are, inter alia, among the causes of youth crime in Turkey. A lack of engagement or intervention by local authorities or municipalities to tackle the problem of youth crime in their regions is a further factor. The problems are aggravated by a trial and prosecution process that takes up to 2 years. When pending trial, children receive almost no training or rehabilitation in institutions, and this impairs their personal development. There is an urgent need to establish a monitoring system which can regularly monitor children who offend and provide support for at least several months after their release. This would help children to reintegrate into society on a more positive level.